PRINSIP-PRINSIP DIGITALISASI LAYANAN INPASSING DOSEN NON-ASN LEMBAGA LAYANAN PENDIDIKAN TINGGI WILAYAH IX - Nurahmad, Nurahmad; Chairunisa, Frida; Samboteng, Lukman (Politeknik STIA LAN Makassar, 2024)
Region IX Higher Education Service Institution, abbreviated as Region IX LLDIKTI, is a work unit within the Ministry of Education, Culture, Research and Technology which is required to provide the best service to the community. Region IX LLDIKTI responded to this demand by transforming to digital services, one of which is the inpassing proposal service. This research aims to determine and analyze the effectiveness of digitizing Region IX LLDIKTI non-ASN lecturer inpassing services. This research is categorized as descriptive qualitative research. The research results show that the implementation of digitalization of Region IX LLDIKTI non-ASN lecturer inpassing services has been effective in the aspects of effectiveness, continuity, efficiency and accountability. However, from the aspects of integration, interoperability and security it is not yet effective and requires improvement and development.